Polynomial chaos Kalman filter for target tracking applications. Issue 2 (17th October 2022) - Kumar, Kundan; Tiwari, Ranjeet Kumar; Bhaumik, Shovan; Date, Paresh
Abstract: In this paper, an approximate Gaussian state estimator is developed based on generalised polynomial chaos expansion for target tracking applications. Motivated by the fact that calculating conditional moments in an approximate Gaussian filter involves computing integrals with respect to Gaussian density, the authors approximate the non‐linear dynamics using polynomial chaos expansion. Second‐order as well as third‐order polynomial chaos expansions were used for approximate filtering, to derive the necessary recursive algorithm and also provide certain algebraic simplifications which reduce the computational burden without significantly affecting the filtering performance. Two comprehensive numerical experiments for multivariate systems, including one for a multi‐model system, demonstrate the potential of the new algorithms.